Breaking through the dumb barrier : an in-depth study of the signals the education system sends to adults in adult education : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education (Adult Education), Massey University - Ledingham, Mary-Adrian (Massey University, 2004)
This thesis explores some of the aspects faced by students who return to learning after a number of years out of the education system in New Zealand. It highlights issues which affect confidence, acceptance, access to information, ability to be heard, finances, workloads, family/friend relationships and the many realities of being an adult student. At the same time it rejoices in the strength, courage and determination shown by those who have dared to return to formal education. A number of case studies and focus groups have been used to develop the critical analysis. Past and present literature has assisted in creating the anchor to the ideas that have emerged. A combination qualitative and interpretive methodology was followed in the production of this thesis. The reality that unfolded was a recognition of also needing to develop a workable framework, as personal assumptions were left behind, new information was discovered and became an integral part of the environment and subsequent information sharing of the researcher and the study participants. The experience of each and every one of this group provided both questions and answers to the usefulness of past and current systems in terms of positive facilitation into education. The failure of the system with its dependency on academic correctness and academic systems will require a more open and transparent re-culturing to enable equitable opportunity, encouragement and practice, or the changes will remain cosmetic and result in sameness. Systems, while necessary, are not in themselves enabling. They can be useful tools to ensure enabling, but if they serve only to disable the very people who are left with no choices but to try to navigate them, then the quest for education can be lost. Education is for people, it is about people, and only if it retains this focus will it continue to educate. Each of the stories in this thesis has at the root of each individual's success, a thread of how "an enabling person" (or persons) made the difference to a system that was fraught with difficulties, that was often cold, inhuman and unbending. These were the lucky ones as, like me, they too came to realise that the system sends very mixed messages to some people. This is not the way it should be.
Keywords: New Zealand; Adult students; Adult education